K-U-TH SYSTEMATICS OF IGNEOUS ROCKS FOR PLANETOLOGICAL COMPARISONS: OCEANIC ISLAND-ARC VOLCANICS ON EARTH VERSUS ROCKS ON THE SURFACE OF VENUS - Nikolaeva O.V. (My University, 1997)
A database of published information was compiled to develop K-U-Th systematics of oceanic island-arc (OIA) volcanic rocks. In order to obtain a pure case of subduction-related oceanic volcanism, the data set for the OIA rocks was narrowed to exclude those arc segments that were subjected to extensional deformations or that contain slivers of continental material in their basement. An analysis of the database showed that petrographically fresh OIA rocks can be discriminated from altered rocks by using either of the following two combined chemical criteria: Fe2O3/FeO < 1.0; H2O+ < 0.8%, and 1.2 < Th/U < 3.4 or L.O.I. < 1.5% and 1.2 < Th/U < 3.4. Based on these criteria, 118 samples of fresh rocks were selected from the database. This data set includes rocks of all geochemical types and series that represent most of the Earth's OIAs, and their major-element signatures are similar to those known for these rocks. The K-U-Th systematics of fresh OIA rocks reveals a progressive enrichment in K, U, and Th from the N-MORB tholeiites to the most evolved OIA rocks, a trend that includes adakites. A branch of the trend formed by the Lesser Antilles rocks shows an abrupt increase in Th and U abundances at 1.4-1.7% K2O. The results of systematization confirm that the fractional crystallization of basaltic magmas had little effect on K, U, and Th fractionation. The K-U-Th systematics was used to estimate the role of various model components that enriched the magmas in large-ion lithophile (LIL) elements. These estimates agree with those based on other data. The rocks become increasingly enriched in U (relative to K) and Th (relative to U) from tholeiitic and calc-alkaline rocks to adakites to high-K calc-alkaline rocks to Lesser Antilles rocks. This sequence can be interpreted as indicating an increasing contribution of the continental (sediment) component compared to the altered (halmyrolytic-hydrothermal) basaltic-slab component. Among the Venusian rocks that were analyzed for K, U, and Th, the Venea 8 material is substantially higher in K than any of the OIA rocks on Earth, whereas four low-K (probably basaltic) rocks are similar to OIA tholeiitic basalts in K content but higher in U and/or Th. Possible petrogenetic scenarios for the moderately LILE-enriched basaltic rocks on Venus are discussed. These rocks differ from terrestrial N-MORB and OIA rocks in that U relatively predominates over K irrespective of the variations in the K/Th and U/Th ratios - a feature that so far remains unexplained.